Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was hoping I could get some help checking my work through.

$\mathcal{L}\{x'(t)\} = sX(s)-1$ and $\mathcal{L}\{x''(t)\} = s^2X(s)-s$

Using the equality $\mathcal{L}\{-tf(t)\} = F'(s)$ we can rewrite the original system as:

$$-\frac{d}{ds}[s^2X(s)-s]+[sX(s)-1]-\frac{d}{ds}[X(s)] = 0$$


$$\frac{X'(s)}{X(s)} = -\frac{s}{s^2+1}$$

Now I'm not sure where to go from here. How can I make this differentiation easier to understand so I can solve the problem? My textbook says the answers should be:

$$X(s) = \frac{C}{\sqrt{s^2+1}}$$

but I don't see how I can get that from my above formulation. Any help?

share|cite|improve this question
up vote 1 down vote accepted

Hint: $$ \frac{X'}{X}=\frac{-s}{s^2+1}\implies \log X=-\frac{1}{2}\log (s^2+1)+\log C\implies \ldots $$

share|cite|improve this answer

Just take your equation $\displaystyle{\frac{X'(s)}{X(s)} = -\frac{s}{s^2+1}}$ a little further: write $X'(s)=\frac{dX}{ds}$ then multiply both sides by $ds$ to get $$\frac{dX}{X} = -\frac{s}{s^2+1}\,ds.$$

Integrate both sides, noting that the left-hand side is of the form $\int \frac{du}{u}$. Solve the result for $X(s)$ and you are done.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.